Circulating tumor cells in patients with head and neck squamous cell carcinoma: Feasibility of detection and quantitation. Issue 11 (17th August 2017) - Kawada, Tomoyuki; Takahashi, Hideyuki; Sakakura, Koichi; Ida, Shota; Mito, Ikko; Toyoda, Minoru; Chikamatsu, Kazuaki
Abstract: Background: The purpose of this study was to present our findings that because circulating tumor cells (CTCs) exist in extremely low numbers, their detection and quantification are challenging. Methods: Peripheral blood samples were collected from 32 patients with head and neck squamous cell carcinoma (HNSCC), and were subjected to the CellSieve Microfiltration Assay using a low‐pressure filtration system. The CTCs captured by the filter were stained with an antibody cocktail (anti‐cytokeratin (CK) 8, 18, and 19, anti‐epithelial cell adhesion molecule (EpCAM), and anti‐CD45 antibodies). Results: The CTCs were detected in 29 of 32 patients (90.6%). Although patients with advanced disease had a significantly higher number of CTCs, the clinical N classification was not associated with the CTC count. After treatment, the CTC count showed a significant decrease. Conclusion: The CTCs were successfully detected and quantified in patients with HNSCC by using a low‐pressure filtration system equipped with precision microfilters. Further studies using a larger number of patient samples and/or molecular analysis of CTCs are warranted.